Effectiveness of radiative heat flux in MHD flow of Jeffrey-nanofluid subject to Brownian and thermophoresis diffusions - Khan, Muhammad Ijaz; Hayat, Tasawar; Waqas, Muhammad; Alsaedi, Ahmed; Khan, Muhammad Imran (Journal of hydrodynamics. Series B, 2019)
Our interest here in this investigation is to explore the thermophoresis and Brownian motion characteristics in flow induced by stretched surface. Electrically conducted Jeffrey material formulates the flow equation. Linear forms of stretching and free stream velocities are imposed. Nonlinear radiation and convective heating processes describe the phenomenon of heat transfer. Passive controls of nanoparticles are considered on the boundary. The compatible transformations produce the strong nonlinear differential systems. The problems are computed analytically utilizing HAM. Convergence domain is determined and major results are concluded for different parameters involved. Heat transfer rate and drag force are also explained for various physical variables. Our analysis reveals that heat transfer rate augments via larger radiation parameter and Biot number. Moreover larger Brownian motion and thermophoresis parameters have opposite characteristics on concentration field.